The Bridge of San Luis Rey - Wilder, Thornton, 1897-1975. (New York : Harper & Row, 1986)
A tiny footbridge in Peru breaks, and five people hurtle to their deaths. For Brother Juniper, a humble monk who witnesses the catastrophe, the question is: Why those five?
Wilson's Fiction.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: Accidents -- Fiction; Accidents -- Fiction; Peru -- Fiction; Peru -- Fiction